بیرى نیشتمانى و گیانى نەتەوەیى لە شیعرى دیالێکتى گۆراندا - سەعید, محەمەد ئەحمەد (Sulaimani Journal for Humanities, 2003)
This research as a modification and historical study deals with a short history about Gorans as “Dialect and Geographical Area “ and sensual Nationality and National spirit in Gerans Dialect poetry at the end of the eighteenth to the twentieth century. This research contains verse-texts of these poets such as Khanai Qubady „Ranjuri , Maulaui , Faqi Qadir , Saudaiy , Khalil Minawar , Kardokhi and Uthman Haurami as evidences and facts to this study so as to analyze a part of these texts and poet's positions about their national cases making Language , Kurds , Kurdistan , Home , Nature and patriotic personalities as a means in to their poetry's specially in this study.